2019
DOI: 10.29252/j.health.10.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Death and Years of Life Lost (YLL) Due to Accidents in Ardabil Province

Abstract: Background & objectives: Accidents are one of the main causes of death worldwide. Iran has one of the highest death rates due to unintentional injuries among countries. The first step in preventing and controlling accidents is collecting basic information about the severity and type of injuries. Methods: This study was conducted to estimate the burden of death due to accidents and injuries in Ardabil province. Death information was extracted from the death registration program of Ardabil University of Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The Odds of traffic crashes mortality in men was1.70 higher than in women. Studies conducted in Iran (15,16,17) and Tanzania (18), India (19) and Thailand (20) have also shown that the proportion of traffic crashes mortality was higher in men. It may due to more participation of men in labor market and more dangerous behavior of males in driving and also because of cultural and religious background in Iran, men can more ride Bicycle, Motorcycle and Heavy vehicles.…”
Section: Discussionmentioning
confidence: 96%
“…The Odds of traffic crashes mortality in men was1.70 higher than in women. Studies conducted in Iran (15,16,17) and Tanzania (18), India (19) and Thailand (20) have also shown that the proportion of traffic crashes mortality was higher in men. It may due to more participation of men in labor market and more dangerous behavior of males in driving and also because of cultural and religious background in Iran, men can more ride Bicycle, Motorcycle and Heavy vehicles.…”
Section: Discussionmentioning
confidence: 96%